When trust is lost: Moral injury in Higher Education - Reynolds, Judith (Critical Studies in Teaching and Learning, 2025)
Transformation, or the lack thereof, student activism, and other day-to-day processes and rules in higher education institutions may lead to situations in which staff witness or are complicit in actions that contradict their sense of right and wrong. As a result, they may experience what is often described as ‘burnout’. It may be more accurate to describe the responses in terms of violations of their moral code, or ‘moral injury’. This conceptual paper draws on the literature on moral injury from other contexts and applies it to the experiences of staff in a higher education context, in South Africa and beyond, through the author’s reflections on her own experiences. Moral injury has numerous potential effects, such as a loss of trust in self or others, feelings of guilt or shame, withdrawal, and interpersonal difficulties. Dealing with moral injury involves grappling with the conditions that create these injuries.